Synthetic glyco-viruses for targeted DNA vaccination vectors - Minall, L (2015)
Viruses are powerful vectors for the delivery of nucleic acids, with applications in gene therapy and vaccination. However, major challenges for this technology include mis-targeting of the vector and neutralization by host antibody responses. Here we show that chemical addition of synthetic glycans to adenovirus (Ad) increased resistance to neutralizing antibodies and other critical host clearance mechanisms. Carbohydrate ligands were synthesised and functionalised with a cyanol methyl thiol group, which was subsequently activated to the amine reactive 2-imino- 2-methoxyethyl (IME). Ads were coated with ligand whilst maintaining virus cogency, with up to 58% of total Ad lysine resides glycosylated. The viral tropism of glyco-Ads was switched to target macrophages and dendritic cells (DCs), with high selectivity for the complementary sugar receptors. In vaccination studies, DC targeted glyco-virus enhanced antigen-specific T cell responses. Thus, chemical glycosylation of the Ad capsid allows modulation of tropism and shielding from sequestration and neutralizing antibodies. Since manipulation of this process is facile, it provides a flexible and potentially universal solution to key obstacles facing the utilization of viral vectors in therapeutic and vaccination contexts.